2022
DOI: 10.2196/35462
|View full text |Cite
|
Sign up to set email alerts
|

An Exercise and Educational and Self-management Program Delivered With a Smartphone App (CareHand) in Adults With Rheumatoid Arthritis of the Hands: Randomized Controlled Trial

Abstract: Background Rheumatoid arthritis (RA) is a prevalent autoimmune disease that usually involves problems of the hand or wrist. Current evidence recommends a multimodal therapy including exercise, self-management, and educational strategies. To date, the efficacy of this approach, as delivered using a smartphone app, has been scarcely investigated. Objective This study aims to assess the short- and medium-term efficacy of a digital app (CareHand) that inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 81 publications
0
16
0
4
Order By: Relevance
“…Virtual care offered additional benefits, including improved treatment adherence, functional status and quality of life 30. However, it is critical that those digital tools are evidence-based and focus on self-management interventions that are developed by healthcare providers and persons with RA to support and empower individuals 31…”
Section: Discussionmentioning
confidence: 99%
“…Virtual care offered additional benefits, including improved treatment adherence, functional status and quality of life 30. However, it is critical that those digital tools are evidence-based and focus on self-management interventions that are developed by healthcare providers and persons with RA to support and empower individuals 31…”
Section: Discussionmentioning
confidence: 99%
“…The 20 studies that were included were about diseases related to the musculoskeletal system (five) [ 16 , 17 , 18 , 19 , 20 ], the nervous system (six) [ 20 , 21 , 22 , 21 , 24 , 25 , 26 ], the proprioception-balance system (two) [ 27 , 28 ], the respiratory system (one) [ 29 ], the cardiovascular system (one) [ 30 ], the pelvic floor control (two) [ 31 , 32 ], and the autoimmune diseases (three) [ 33 , 34 , 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Adjunctive treatments such as assessment by hand occupational therapy, structured exercise programs, and utilizing mobile health (mHealth) interventions combining home exercise programs and self-management recommendations have been shown to improve overall joint function, pain levels, and satisfaction compared with usual care [31–33]. Significantly, a recent study evaluating custom-made foot orthoses reported that not only were there expected reductions in foot ( P < 0.001) and leg pain ( P = 0.012), but also pain reduction was noted in the arms and hands ( P = 0.014) [34 ▪ ].…”
Section: Adjunctive Management Strategiesmentioning
confidence: 99%